2003
DOI: 10.1046/j.1365-2648.2003.02650.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse managers' professional networks, psychosocial resources and self‐rated health

Abstract: The study showed that nurse managers exposed to high job demands had elevated odds for low self-rated health, regardless of level of psychosocial resources within or outside work. Two-thirds of the nurse managers who were affiliated to professional networks did not consider this a supporting factor in their management work. Those with low job support had increased odds for sick-leave compared with those with high support. No significant associations were found between psychosocial characteristics and salary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 19 publications
0
20
1
Order By: Relevance
“…Lindholm et al, in their study about Sweden nurse managers, found no significant association between psychosocial characteristics and salary either [28].…”
Section: Occupational Depressive Symptoms Of Nurse Managers O R I G Imentioning
confidence: 85%
See 1 more Smart Citation
“…Lindholm et al, in their study about Sweden nurse managers, found no significant association between psychosocial characteristics and salary either [28].…”
Section: Occupational Depressive Symptoms Of Nurse Managers O R I G Imentioning
confidence: 85%
“…Concerning their health, a study carried out by Lindholm et al in Sweden investigated self-rated health, sick leave of nurse ma nagers according to their professional networks, psychosocial work conditions, job support, social network and support. An association was found between high job demands and low self-rated health [28]. A study carried out in Japan showed that a lack of assertiveness and satisfaction was associated with burnout among Japanese nurse managers [29].…”
Section: Introductionmentioning
confidence: 95%
“…Lindholm et al (2003) Sweden Survey Low levels of support received by professional networks-measured in terms of affiliation/nonaffiliation-increased odds for nurses' low job satisfaction and selfrated health at work. Lindholm et al (2004) Sweden Survey…”
Section: Appendix (Continued)mentioning
confidence: 99%
“…Availability of social support has been suggested to mitigate the resulting strain of such work situations. In managers, social support has been associated with decreased stress and strain [22][23][24], fewer 4 symptoms of burnout [25], higher self-rated health [26], lower physiological stress [27], and less sickness absence [28]. Recent studies have also shown that managers' social support is positively related to other work-related issues besides stress and health, such as leadership development [29][30][31], workplace learning [33], work-life balance [22,34] and performance [35][36].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Receiving social support may not always be a good thing; research has shown that it may also be associated with increased stress [4,6,26,[63][64]. Two hypotheses have been formulated to explain such conflicting findings [6,[65][66][67].…”
Section: Literature Reviewmentioning
confidence: 99%